Comparative study on certain aspects of the biology of Macrobrachium Equidens Equidens (Dana, 1852) and M. Equidens Pillaii Jayachandran, 1989 - Anitta Sebastian (Department of Fishery Biology, College of Fisheries, 1993)
The aim of the present study has been to establish the taxonomic status of Macrobrachium equidens equidens (Dana, 1852) (spotted variety) and M. equidens pillaii Jayachandran, 1989 (striped variety) which co-exist in Cochin backwaters, by undertaking investigations on certain aspects of their biology. The two populations differ in colouration, length and arrangement of teeth in the rostrum, nature of carapace, telson, proportions of different podomeres and nature of pubescence of fingers of 2nd cheliped. Considerable differences in the growth patterns of the two populations also have been noticed in the characters, such as, rostrum, cephalothorax, carapace, width of carapace and ischium, merus, carpus, propodus, palm and fingers of 2nd cheliped. The meristic studies revealed that the arrangement of rostral teeth is specific for each population. Similarly these two populations differ in the length-weight relationships also. The SDS polyacrylamide gel electrophorogram showed clear difference in the number and position of bands in the two populations. Though the early part of oogenesis of the two populations showed similarity, considerable differences have been observed in the yolk deposition. The present investigation revealed that the two populations differ drastically in respect of all the characters studied and therefore are to be considered as two distinct species. The striped variety had been described as new species twice before of which the name "sulcatus” preoccupies any other name. Therefore the present investigation proposes the names for the two species as M. equidens (Dana, 1852) and M. sulcatus (Henderson & Matthai, 1910).